Застапеност на хиподонцијата кај популацијата во Република Македонија - Поп Ацев, Дарко (Стоматолошки факултет, УКИМ, Скопје, 2015)
Hypodontia is a condition at which the patient is missing one or more teeth, due to their failure to develop. Missing teeth are one of the most common developmental anomalies. This condition is an aesthetic as well as functional deficiency. The prevalence of missing teeth depends on the ethiological factors, gender, race, geographic and demograpjic distribution. Most common congenital tooth absence is affecting the teeth that are last developed in each group ( lateral incisors, second premolars, third molars). The aim of this study was to assess the prevalence and pattern of congenital missing teeth in permanent dentition among the population of Republic of Macedonia and through a review of the literature to compare it with other countries and regions in the world. Also one part of the study was to verified if there is a mutation on WNT10A gene among patients with tooth agenesis. Though a retrospective, cross-sectional study was made. We reviewed panoramic radiographs of 8160 orthodontic patients (3671 men and 4489 women), aged 8-18 years old. Third molars were excluded from the study. The data were analyzed using a chi-square test with Statistica 7.0 program. The prevalence of hypodontia was 7,52%. The difference between genders was with high significance (p=0,0009). The difference among two ethnic groups, Macedonian and Albanian, was statistically significant, with predomination in Albanians (p=0,0266). The most common missing tooth was mandibular second premolar, followed by maxillary lateral incisor. From ten probands that were made among patients with hypodontia, in four of them mutation of WNT10A gene was present. This confirms the role of the WNT10A gene in dentofacial development, as a possible factor for tooth agenesis.
Докторска дисертација одбранета во 2015 година на Стоматолошкиот факултет во Скопје, под менторство на проф. д–р Јулијана Ѓоргова.
Keywords: hypodontia, prevalence, tooth agenesis, mutation, WNT10A